Kehidupan buruh perkebunan kopi di Dampit tahun 1870-1930 - Syarifudin, Muhammad Bahtiar; Sapto, Ari; Hudiyanto, Reza (Historiography: Journal of Indonesian History and Education, 2023)
The end of the cultuurstelseel policy and the emergence of the Agrarian Law of 1870 led to the development of plantations on a large scale, because this system gave private parties the right to develop their business in the field of export commodities by leasing native land. This has caused many people to migrate from villages to plantation areas to work as plantation labourers. This study attempts to describe the development of plantations which have begun to expand into inland areas on the island of Java, especially in Malang. Besides that, how is the life of plantation workers as plantation workers, where plantation workers occupy the lowest strata in stratification. This paper is reviewed using the historical method with sources that have been collected in the form of photo archives and documents, as well as several written sources in the form of books and articles. The policies implemented by the Dutch East Indies government greatly influenced the life of the indigenous people, especially from a social and economic point of view of the community itself. Berakhirnya kebijakan cultuurstelsel dan munculnya UU Agraria tahun 1870 menyebabkan perkembangan perkebunan secara besar besaran, karena sistem tersebut memberikan hak kepada pihak swasta untuk mengembangkan bisnisnya dibidang komoditas ekspor dengan cara menyewa tanah bumiputera. Hal itu menyebabkan banyaknya migrasi masyarakat dari desa menuju ke kawasan perkebunan untuk bekerja sebagai buruh perkebunan. Kajian ini berusaha menggambarkan perkembangan perkebunan yang mulai meluas ke area pedalaman di pulau Jawa terutama di Malang. Selain itu bagaimana kehidupan buruh perkebunan sebagai tenaga kerja yang menempati strata paling bawah dalam stratifikasi. Tulisan ini dikaji menggunakan metode sejarah dengan sumber yang sudah dikumpulkan berupa arsip foto maupun dokumen, serta beberapa sumber tertulis berupa buku dan artikel. Kebijakan yang diterapkan oleh pemerintah Hindia-Belanda sangat mempengaruhi kehidupan masyarakat bumiputera, terutama dari segi sosial maupun ekonomi masyarakat itu sendiri.